2016
DOI: 10.1038/srep24214
|View full text |Cite
|
Sign up to set email alerts
|

Citrus unshiu peel extract alleviates cancer-induced weight loss in mice bearing CT-26 adenocarcinoma

Abstract: Skeletal muscle atrophy is a critical feature of cancer-induced cachexia, caused by pro-cachectic factors secreted by host cells and tumor cells. Therefore, blockade of these factors has considered a reasonable target for pharmacological and nutritional interventions to prevent skeletal muscle loss under cancer-induced cachexia. Citrus unshiu peel (CUP) has been used for treating the common cold, dyspepsia, and bronchial discomfort and reported to have pharmacological activities against inflammation, allergy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…In this study, we revealed that NYT and citrus unshiu peel activated OX1R using an in vitro assay. Kim et al have shown that citrus unshiu peel extract alleviates cancerinduced weight loss in mice bearing CT-26 adenocarcinoma (60). Although further studies using cancer cachexia-anorexia model animals are required, these previous and our present data suggest that NYT might improve cancer cachexia-anorexia via the activation of OX1R.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we revealed that NYT and citrus unshiu peel activated OX1R using an in vitro assay. Kim et al have shown that citrus unshiu peel extract alleviates cancerinduced weight loss in mice bearing CT-26 adenocarcinoma (60). Although further studies using cancer cachexia-anorexia model animals are required, these previous and our present data suggest that NYT might improve cancer cachexia-anorexia via the activation of OX1R.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, while the possibility of anti-cancer activity of C. unshiu peel extract based on the increase of immune activity and anti-inflammatory effect has been raised (31,32), little research has been performed on the mechanism of cancer cell proliferation inhibition. In this study, it was demonstrated that EECU treatment induces the apoptosis of human bladder cancer T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study on a tumor-bearing mouse model has shown that C. unshiu peel (Chimpi) extract inhibits tumor growth, which was associated with an increased production of cytokines such as interferon-γ and tumor necrosis factor-α (31). In addition, Kim et al (32) reported that C. unshiu peel reduces systemic inflammation in tumor-bearing mice and inhibits the production of pro-cacheche factors in tumors with the prevention of skeletal muscle atrophy and weight loss. It has also been reported that polysaccharides or flavonoids found in the C. unshiu peel can inhibit the metastasis of cancer cells (33,34); however, the evidence for the therapeutic potentials of C. unshiu peel against human cancer cells and the molecular pathways involved in suppression of cancer cell apoptosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The previous researches have elucidated that several compounds of citrus plants possess a wide range of pharmacological effects, such as anti-inflammation, antioxidation, anticancer, and neuroprotection [1,2]. Specifically, the dried peel of citrus, a functional health food ingredient, is used as a traditional herbal ingredient to treat various digestive dysfunctions, involving dyspepsia, abdominal distension, and vomiting in East Asia [3]. Further, few in vivo studies on citrus extracts have indicated their ameliorative effects in disturbances of Nutrients 2020, 12, 673; doi:10.3390/nu12030673 www.mdpi.com/journal/nutrients gastrointestinal microbiota and obesity conditions.…”
Section: Introductionmentioning
confidence: 99%